International economics - Carbaugh, Robert J. (South-Western/Cengage Learning, 2013)
Carbaugh demonstrates the relevance of theory through real-world economic issues. Theoretical discussions are presented in both verbal and graphical terms, making the book highly accessible to students with little economics background.